The financial status, financial problems and personal well-being of urban poor youths - Sabri, Mohamad Fazli; Moga Dass, Thinagaran (Human Resource Management Academic Research Society, 2017)
The fast growing economic of Malaysia has impacted more urbanization as the Malaysians migrate to cities to seek employment and education opportunities and resulted in rising living cost. Youth plays a big role in building the nation and rising living cost is one of the financial challenges as they are unable to practice saving behaviour due to their environmental and lead to the use of exploitative lenders and to financial instability and it may leads to financial stress. This study is to to assess their current financial status, financial problems and personal well-being. This study is conducted with 500 youths from 18-40 years old living in low-cost flats with income below RM3000. The respondents consist of 48.7% male and 51.3% female; 70.2% were Malays, 13.1% Chinese and 14.9% Indian and 1.4% consisting of other races. The youths’ main saving and investment portfolio is Employee Provident Fund (EPF) with 69% and less diversification in investment. Urban youths (69%) mostly own motorcycle as asset followed by house (32%), and jewelleries (16.1%). In contrast, 54.3% of them are engaged with mortgage loans and 33.3% with personal loans; the asset to debt ratio revealed that 47% of the have debts more than asset and 34% youths are inadequate of income. The main financial problem is paying bills late (88.9%) and spirituality scores the highest ranking in personal well-being with mean 7.26. Enhancing financial literacy and molding good financial behavior need to be inculcated to the youths as a coping strategy.